Stabilization of K2CO3 in vermiculite for thermochemical energy storage. (May 2020) - Shkatulov, A.I.; Houben, J.; Fischer, H.; Huinink, H.P.
Abstract: Thermochemical energy storage (TCES) is an emerging technology promising for domestic applications. Recently, K2 CO3 was identified and studied as a TCES material. In this work, the composite "K2 CO3 in expanded vermiculite" (69 wt. % of the salt) was prepared and studied for thermochemical energy storage bearing in mind its application for space heating. The hydration rate was found to be higher for the confined K2 CO3 in comparison with K2 CO3 granules of the same size. While morphology and texture of the composite alter after 74 hydration/dehydration cycles, its chemical composition and average grain size do not change. The energy storage density of the composite bed can reach 0.9 GJ/m 3 (250 kWh/m 3 ) for cycles with deliquescence which makes the composite an inexpensive thermochemical material for space heating. Stable conversion for deliquescence conditions was shown for at least 47 cycles. Highlights: Chemical, textural and bed stability of the composite K2 CO3 /vermiculite are studied. The K2 CO3 self-dispersion is found in the course of the cycling. Use of the matrix enhances hydration rate. Heat storage density in a bed reaches 0.9 GJ/m 3 for K2 CO3 deliquescence conditions.